Whole-genome sequencing of SARS-CoV-2 reveals diverse mutations in circulating Alpha and Delta variants during the first, second and third waves of COVID-19 in South Kivu, east of the Democratic Republic of Congo - Ntagereka, P.B.; Oyola, Samuel O.; Baenyi, S.P.; Rono, Gilbert K.; Birindwa, A.B.; Shukuru, D.W.; Baharanyi, T.C.; Kashosi, T.M.; Buhendwa, J.C.; Bisimwa, P.B.; Kusinza, A.B.; Basengere, R.A.; et al. (Elsevier, 2022)
Objectives: Using whole genome sequencing of SARS-CoV-2 to identify variants circulating in DRC and obtaining molecular information useful for diagnosis, improving treatment and general pandemic control strategies.